Self-Directed Learning in EFL During Covid-19 Pandemic: Teacher’s Perception and Students’ Learning Autonomy - Ni Luh Made Purnia Adi; Luh Putu Artini; Luh Gede Eka Wahyuni (Universitas Pendidikan Ganesha, 2021)
Due to the global outbreak of coronavirus disease (COVID-19), new regulations require students to study from home so that students must be able to study independently. This study aimed to analyze teachers' perceptions of self-directed learning (SDL) and SDL components that can be identified from online learning activities assigned by teachers during the COVID-19 pandemic. This research was designed in the form of embedded mixed-method research. An English teacher at a high school was selected as a participant. Furthermore, data were collected through questionnaires, observations, and classification tables. The results showed that: 1) with a score of 4.00, teachers perceive themselves as